PENGORGANISASIAN KEGIATAN EKTRAKULIKULER PAUD IT BAITUL IZZAH KOTA BENGKULU - Siti Soleha; Agus Zainal Rachmat; Suardi Jasma (Jurnal Pendidikan Sepanjang Hayat, 2020)
This research is a qualitative case study research which aims to describe the extracurricular organization in PAUD IT Baitul Izzah Bengkulu City. The subjects in this study were the principal, the total extracurricular coordinator and the 4th extracurricular assistant teacher. This research was conducted at PAUD IT Baitul Izzah which is located on Jl. Construction of No.17 Baitul Izzah Grand Mosque Complex in Bengkulu City on 02 July-29 August 2020. Data collection was carried out through interviews, observation and documentation. Data were analyzed and validated using triangulation data validity techniques. From the results of the research, organizing extracurricular activities at PAUD IT Baitul Izzah was grouped into four extracurricular activities, namely, submitted to each extracurricular companion teacher, then submitted by the accompanying teacher, divided into groups based on age and grade level. As for the placement of people in extracurricular activities, Unbeatable with extracurricular activities, selected first to see the talents and interests of accompanying teachers or to become extracurricular participants, as evidenced by the SK PAUD IT Baitul  Izzah. Provision of tools in extracurricular activities carried  out by schools  and assisted by extracurricular student guardians.  Keywords: Organizing, Extracurricular, PAUD